MicroRNA-410-3p Binds to TLR2 and Alleviates Myocardial Mitochondrial Dysfunction and Chemokine Production in LPS-Induced Sepsis - Tongkun Zuo; Qing Tang; Xiangcheng Zhang; Futai Shang (Elsevier, 2020)
Mitochondrial dysfunction and chemokine production have been reported to be involved in the pathogenesis of sepsis. Our initial bioinformatics analysis identified differentially expressed TLR2 in sepsis and the upstream regulatory microRNA-410-3p (miR-410-3p). Hence, the current study was performed to characterize the potential mechanism by which miR-410-3p modulates mitochondrial dysfunction and chemokine production in lipopolysaccharide (LPS)-induced mice in vivo and cardiomyocytes in vitro. Next, we identified that miR-410-3p was downregulated, while TLR2 was upregulated in LPS-induced mice and cardiomyocytes. In addition, miR-410-3p was confirmed to target and inhibit the TLR2 expression. Thereafter, gain- or loss-of-function experiments were conducted to investigate the effect of miR-410-3p and TLR2 on mitochondrial function and chemokine production. TLR2 knockdown or miR-410-3p overexpression was found to alleviate mitochondrial membrane damage and mitochondrial swelling, in addition to augmenting the levels of adenosine triphosphate, mitochondrial membrane potential, and the expression levels of CCL7, CCL5, CXCL1, and CXCL9 in vivo and in vitro. In conclusion, miR-410-3p-mediated TLR2 inhibition alleviated mitochondrial dysfunction and reduced chemokine production in LPS-induced experimental sepsis. Therefore, the overexpression of miR-410-3p may represent a potential strategy for the treatment of sepsis-induced myocardial injury.